Spirituality Batetulak: Construction of Social Piety and Solidarity of the Rembiga Muslim Community - Subhan Subhan; Ahmad Fauzan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study discusses the discourse of traditional rituals in the community Sasak village batetulak Rembige in Mataram Nusa Tenggara Barat. This ritual has been going hundreds of years ago as a cultural heritage of the early generations of Islam in Rembige spreader. Besides aiming to prevent reinforcements or disasters that can happen anytime Rembige communities and villages, this ritual also aims to welcome the new year of Islam. On his way there were a bunch of people who see batetulak ritual conflict with Islamic law or heresy, then there are the related discourse of this ritual.The results showed that the ritual discourse batetulak present in spaces recitals (liqo '), religious lectures, coffee shop chats, meetings of customs, the cultural chatter and text / speech appropriate government officials batetulak ritual. The existence of ritual discourse batetulak caused by three factors: education, modernity and religious purification. Before modernity and Wahabi ideology is present in public life Rembige batetulak never questioned ritual, this ritual as a value system that has been inherited from the early generations of Islam in Rembige. The entry of modernity and Wahabi ideology spawned a variety of rituals batetulak discourse in society Rembige, it has implications on the pros and cons of the ritual batetulak. Implications batetulak ritual discourse is the emergence of discourse batetulak struggle on the Rembige, struggles happen to each person who memored Rembige there is a good variety ideology Wahabi ideology, modernity and culture of Rembige own ideology